Antimicrobial activity of Piper arboreum and Piper tuberculatum (Piperaceae) against opportunistic yeasts - Regasini, Luis Octávio [UNESP]; Cotinguiba, Fernando [UNESP]; Morandim, Andreia De Araújo [UNESP]; Kato, Massuo Jorge; Scorzoni, Liliana [UNESP]; Mendes-Giannini, Maria José [UNESP]; Bolzani, Vanderlan Da Silva [UNESP]; Furlan, Maysa [UNESP] (My University, 2009)
In the scope of our ongoing research on bioactive agents from natural sources, 24 extracts and fractions obtained from Piper arboreum Aub. and Piper tuberculatum Jacq. (Piperaceae) were screened for antifungal activity by using broth microdilution method. The current investigation reveals that P. arboreum extracts and fractions were more effective against Candida krusei and Candida parapsilosis than Cryptococcus neoformans. The growth of Candida albicans was weakly affected by all the tested extracts and fractions. The strongest effects were observed for hexane and ethyl acetate fractions from leaves of P. arboreum, with MIC values (in μ g/ml) of 15.6 and 31.2 μ g/ml against C. krusei, respectively. Additionally, phytochemical investigation of the hexane fraction of P. arboreum leaves furnished 3 pyrrolidine amides; piperyline, 4,5-dihydropiperyline and tetrahydropiperyline, which could be responsible, at least in part for the observed antifungal activity. The most active compound, tetrahydropiperyline, displayed MIC values of 15.6 μ g/ml against C. krusei, C. parapsilosis and C. neoformans. © 2009 Academic Journals.
Keywords: Antifungal; Antimicrobial; Candida; Cryptococcus neoformans; Piper arboreum; Piper tuberculatum; Piperaceae